Розробка мехатронного гідроагрегата з гібридним керуванням виконавчим механізмом - Федоренко, І. М. (НТУ "ХПІ", 2009)
Приведены результаты аналитического обзора схемных решений современных мехатронных гидроагрегатов технологических и мобильных машин. Предложена перспективная схема и аппаратная реализация мехатронного гидроагрегата с частотным управлением вращения приводного асинхронного электродвигателя и внутренней обратной связью, которая позволяет создать гибридную схему регулирования производительностью насоса, расширить область применения гидроагрегата и повысить его надежность.

Results of analytical review of schematic decisions of modern mechatronical hydraulic aggregates of technological and mobile machines are instanced. The perspective scheme and device realization mechatronical the hydraulic aggregates with frequency management of rotation of the asynchronous electric motor and an internal feedback which allows to create the hybrid scheme of regulation by productivity of the pump is offered, to expand a area of application of the hydraulic aggregates and to increase its reliability.
Keywords: ККД; об’ємний насос; регулюючо-розподільний пристрій; LS модуль; гібридне керування